An irreducible Heegaard diagram of the real projective 3-space p3 - Young Ho Im; Soo Hwan Kim (International Journal of Mathematics and Mathematical Sciences)
We give a genus 3 Heegaard diagram H of the real projective space p3, which has no waves and pairs of complementary handles. So Negami's result that every genus 2 Heegaard diagram of p3 is reducible cannot be extended to Heegaard diagrams of p3 with genus 3.